Análise comparativa de ferramentas low-code para desenvolvimento de software - Siqueira, Victor Caio Araujo (2024)
The development of software has undergone significant transformations, with the increasing demand for agile and efficient solutions and the shortage of qualified developers. In this context, low-code platforms emerge as a promising alternative, enabling the development of applications with little to no coding, thus offering a solution to this reality. This study conducted a comparative analysis of different low-code development platforms, such as Directus, Strapi, Parse, Supabase, and Firebase, aiming to identify the most suitable for backend solution development. Using a practical implementation methodology, characteristics such as ease of setup, performance, learning curve, size of the support community, among others, were evaluated. The research highlighted the benefits of low-code platforms, such as agility, cost reduction, and ease of maintenance, but also pointed out limitations, such as scalability and fragmentation across platforms. The results indicate that, despite the advantages, the choice of the ideal tool should consider the specific context of the project, making a careful analysis of the needs and available features essential. This study contributes to the understanding of the possibilities and challenges of low-code platforms in software development, offering resources for decision-making by developers and organizations.